Protecting Florida Horses from Mosquitoes - Cynthia C. Lord; Roxanne Rutledge Connelly (EDIS)
This document discusses methods to protect horses in Florida from mosquito-borne diseases like Eastern Equine Encephalitis and West Nile virus. It covers mosquito biology, breeding habits, and control strategies, including population reduction, stabling, premise sprays, traps, physical barriers, and topical insecticides or repellents. The document emphasizes the importance of reducing mosquito breeding sites around stables and using appropriate insecticides and repellents to protect horses from mosquito bites. Date first published: July 2001.